2023
DOI: 10.1007/s10654-023-00981-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported insomnia symptoms, sleep duration, chronotype and the risk of acute myocardial infarction (AMI): a prospective study in the UK Biobank and the HUNT Study

Abstract: Insomnia and short/long sleep duration increase the risk of AMI, but their interaction with each other or with chronotype is not well known. We investigated the prospective joint associations of any two of these sleep traits on risk of AMI. We included 302 456 and 31 091 participants without past AMI episodes from UK Biobank (UKBB; 2006–10) and the Trøndelag Health Study (HUNT2; 1995–97), respectively. A total of 6 833 and 2 540 incident AMIs were identified during an average 11.7 and 21.0 years follow-up, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 53 publications
(71 reference statements)
6
12
5
Order By: Relevance
“…Nonetheless, our finding showing evidence of an adverse causal effect of insomnia symptoms and a weak adverse causal effect of short sleep on the risk of AMI is consistent with prior observational [9,10,12] and MR research [12,23,24]. Our finding yielding evidence of a protective causal effect of long sleep on the risk of AMI contradicts with prior observational studies [9,12], but aligns with a weak concordant effect shown by another MR study [23]. Long sleep may be an indicator of poor health status, being closely associated with depression, poor sleep quality, sedentary lifestyles and underlying comorbid conditions [47,48], and so residual confounding or reverse causation may have biased previous observational findings.…”
Section: Causal Effects Of Individual Sleep Traits On the Risk Of Amisupporting
confidence: 92%
See 4 more Smart Citations
“…Nonetheless, our finding showing evidence of an adverse causal effect of insomnia symptoms and a weak adverse causal effect of short sleep on the risk of AMI is consistent with prior observational [9,10,12] and MR research [12,23,24]. Our finding yielding evidence of a protective causal effect of long sleep on the risk of AMI contradicts with prior observational studies [9,12], but aligns with a weak concordant effect shown by another MR study [23]. Long sleep may be an indicator of poor health status, being closely associated with depression, poor sleep quality, sedentary lifestyles and underlying comorbid conditions [47,48], and so residual confounding or reverse causation may have biased previous observational findings.…”
Section: Causal Effects Of Individual Sleep Traits On the Risk Of Amisupporting
confidence: 92%
“…Nonetheless, our finding showing evidence of an adverse causal effect of insomnia symptoms and a weak adverse causal effect of short sleep on the risk of AMI is consistent with prior observational [9,10,12] and MR research [12,23,24]. Our finding yielding evidence of a protective causal effect of long sleep on the risk of AMI contradicts with prior observational studies [9,12], but aligns with a weak concordant effect shown by another MR study [23].…”
Section: Causal Effects Of Individual Sleep Traits On the Risk Of Amisupporting
confidence: 83%
See 3 more Smart Citations